Relationship Between Indoor Air Quality and Sick Building Syndrome in Post Office Building in Bandung - Yudi Prana Hikmat; Ismail Wellid; Kasni Sumeru; Salma Dzakiyah Az-zahro; Mohamad Firdaus bin Sukri (Bandung State Polytechnic (Politeknik Negeri Bandung), 2021)
Sick building syndrome (SBS) is a collection of symptoms experienced by buildings occupants such as headaches, mucous, membrane irritation, respiratory problems and fatigue. A building is claimed to have SBS if more than 20% of building occupants experience symptoms. Poor indoor air quality contributes to SBS in the building. This study aims to investigate the correlation between indoor air quality and SBS symptoms in 1st and 2nd floors of the Post office building in Bandung. The study used quantitative methods with a cross sectional study design. Data collection was carried out using particle counter, thermometer, lux meter and anemometer to measure the indoor air quality, while the questionnaire utilized random sampling technique with 119 respondents. The results of the primary data were compared with the air quality standard from Minister of Health No. 1077, 2021. The results of the Statically Compare Means and Independent T-test showed that the p-values of the temperature on the 1st floor and 2nd floors were 0.437 and 0.000, respectively. Meanwhile the p-values of PM10 and PM2.5 on the 1st and 2nd floors were 0.005 and 0.290 and 0.004 and 0.364, respectively, and the p-values of the lighting on the 1st and 2nd floors were 0.002 and 0.015. It indicates that there is a significant relationship between concentrations of PM10 and PM2.5 on the 1st floor with SBS symptoms and the temperature and humidity on the 2nd with SBS symptoms. Since 29 peoples (24% of the building’s occupants) experienced SBS, the building was considered to have a significant potential to cause SBS to its occupant.